PENGARUH KARATERISTIK KEPALA DAERAH, UKURAN PEMERINTAH, DAN TEMUAN AUDIT TERHADAP KINERJA KEUANGAN DAERAH - Tabita Tandiseru, Ai Andi; Ashedica Pesudo, David Adechandra (Jurnal Akuntansi dan Pajak, 2023)
Financial performance is a manifestation of regional achievements in a certain period related to regional finances. This study has a purpose, namely to examine whether there is an influence of the characteristics of regional heads, government size, audit findings on the financial performance of local governments in districts/cities on Sulawesi Island in 2018-2020. The population used in this study is from the district/city government on the island of Sulawesi. The sampling method used purposive sampling. This study uses secondary data with the data source used, namely the financial reports of the district/city governments on the island of Sulawesi in 2018-2020. Hypothesis testing in this study uses multiple linear analysis using the SPSS program. The results showed that the government size variable had a positive and significant effect on the government's financial performance. The characteristic variable has no influence on the financial performance of the local government. The results of the BPK audit findings variable test have a negative and significant effect on financial performance.